Optimalisasi Edukasi Kesehatan dengan Pemeriksaan Spirometri pada Kegiatan Pengabdian Masyarakat - Hadisono, Hadisono; Santoso, Alexander Halim; Wijaya, Bryan Anna; Hendrianto, Rifandra Rifqi Adi; Johan, Richver Framanto (PT. Riset Press International, 2026)
Chronic obstructive pulmonary disease (COPD) is a health problem with increasing prevalence in aging populations, contributing to a decline in the quality of life among older adults. This community service program aimed to optimize health education through spirometry assessments in an urban population. The activity was conducted at Asisi Church, South Jakarta, involving 99 participants (mean age 71.85±8.08 years; majority female 71.7%). Pulmonary function was assessed by spirometry, measuring FVC, FEV1, and FEV1/FVC ratio. Results showed that most participants exhibited a restrictive pattern, with reduced FVC (mean 58.8%; 89.9% decreased) and FEV1 (67%; 77.8% decreased), although the FEV1/FVC ratio remained within the normal range (91.9%). These findings highlight that the decline in lung capacity is more prominent in urban older adults. Integrating simple screening with health education sessions proved effective as a promotive–preventive strategy to raise community awareness regarding regular monitoring of lung function and adopting sustainable healthy lifestyles.